Paciente de sexo femenino de 64 años de edad con hipertensión arterial, esteatosis hepática y presenta obesidad mórbida, quemaduras de grado II. - Rodriguez Lopez, Arley Geraldine (2020)
Morbid obesity is a frequent chronic nutritional disorder, where poor diet and a sedentary life are the risk factors for the various diseases that occur such as arterial hypertension, hepatic steatosis, which limit life expectancy and deteriorate the quality of life. same. Where the general objective was to maintain the nutritional status of the patient. To develop the clinical case an observational, transversal and descriptive methodology was used. Because the clinical history, physical examination and monitoring of the patient's biochemical tests were taken into account. The present case study is based on a 64-year-old female patient who is admitted to the hospital for burns of II degree, with a personal pathological history of morbid obesity, hepatic steatosis and arterial hypertension, in which the diagnosis is used Integral nutritional. The case study is concluded by improving the nutritional status where a diet was used according to the requirements and needs of the patient.